(untitled) (Journal Of Educational and Psychological Researches, 2016)
The figure of personality modes determines its privileged style in the use of modern and advanced technological tools in the process of changing and developing in order to keep up with that. The proses of selection and choosing administrators in the appropriate places are the most important functions of senior management because it is easy to adopt factory buildings or establishments But this is a human world as that of machines world. So it is required to have people in the process of changing those who have a time, Knowledge, skill, ability and strong administrative personal skills, those people (leaders) should to put a clear vision for the selection and application of the change efforts and to create the necessary climate and incentives for the process may be long and complex. The researcher’s aim of this study is to find: • Identify the levels of each of the six personal style patterns according to Holland’s theory of the three categories. • Identify the level of administers changes according to the three categories. • Significant statistical differences in each style of personal patterns according to Holland’s theory depending on the variables of sex, years of administrative service of the three categories. • Significant statistical differences in the administers changes scale depending on the variables of sex, years of administrative service of the three categories. • Correlational relationship between each style of personal patterns according to Holland’s theory and administers changes of the three categories. • The contribution of each style of personal patterns of administers changes measurement of the three categories. Research limits: The current research on the following categories is limited (administers in Ministry of Planning in the Government of Kurdistan-Iraq , and heads of departments in Salahaddin University-Erbil, and the head of primary and high schools in the city of Arbil) in the capital of Irbil for the academic year (2014 and 2015) according to sex and years of administrative services. Research Procedures: - The six personal style patterns of Holland’s theor which was developed by (gafur, 2011) also (Hamad, 2007) and depending of literatures wich related to this subject was used current study , also researcher adopted on a scale (Ismail, 2007) for the variable of administers changes, then to checking the two measures the following steps were taken: (extract honesty Virtual, discriminatory power, the degree of correlation paragraph degree pattern and the total score of the scale, the degree of relationship of each category with the total degree of the scale, and stability in a way retail midterm and Alfa-kronbach). -Appling a survey also the validity to the scale of personal patterns and then the final application of the two measures on three categories were applied with participants no. (462) of administrators in the Kurdistan governmental establishment. Statistical methods: Data collected in the study was analyzed using the Statistical Package for the Social Sciences (SPSS), version 19. Including statistical means unless: (T-test samples for two independent samples, Pearson correlation coefficient, t-test for one sample, Spearman Brown equation, Alfa-kronbach equation, analysis of variance duo, multiple regressions) . Results: 1-There were statistically significant differences all six personal patterns according to the theory of Holland at the level of significance (0.001) of the administers in three categories and the differences were all for the benefit of the sample. • There were statistically significant a difference to the variable of administers changes at the level of significance (0.001) with the directors of the three categories and the differences were all for the benefit of the sample. 3- There were no statistically significant differences at the level of significance (0.05) to all six personal patterns by sex and administrative years of service of the three categories, because the value of calculated T was smaller than the value of T in tabular to all personal patterns. • There were no statistically significant differences at the level of significance (0.05) to administers changes variable depending on the sex and administrative years of service of the three categories, because the value of calculated T was smaller than the value of T in tabular to all personal patterns. • There were no statistically significant among the six personal patterns according to Holland’s theory and administrators changes at any level of statistical significance, except statistical significant were found as a positive correlation between analytical pattern and administrators changes at the level of significance (0.05) and (0.01) of the Ministry of Planning administers and presidents of the department, Also results showed there were no statistically significant relationship between styles (artistic, traditional, adventurer) with administrators changes at any level of statistical significance. While the results suggest a positive relationship between patterns (realistic, analytical, social) at levels of significance (0.05) and (0.01) of the heads of primary and high schools . 6-Statistically significant contributions were found of some of the six personal patterns in administrators changes with the managers of the three categories.